RELACIÓN ENTRE LAS ADAPTACIONES CURRICULARES Y SU IMPACTO EN EL RENDIMIENTO ACADÉMICO EN ESTUDIANTES CON NECESIDADES EDUCATIVAS ESPECÍFICAS DE 4TO GRADO DE EDUCACIÓN BÁSICA DE LA UNIDAD EDUCATIVA MANUEL CÓRDOBA GALARZA. - YEPEZ AVILEZ ZENEN ALDAHIR (2024)
This study was conducted with the general objective of determining the impact of curricular adaptations on the academic performance of fourth-grade students with specific educational needs (SEN) at the Manuel Córdoba Galarza Educational Unit. The addressed issue focuses on educational inclusion and the need to adapt the curriculum to ensure that all students, regardless of their abilities, have access to quality education. The methodology used combined quantitative and qualitative analysis tools to evaluate the effectiveness of curricular adaptations. Surveys were conducted with teachers and academic performance analyses were carried out to identify the types and frequency of use of the adaptations, as well as their impact on the students. The study's results revealed that curricular adaptations have a significant impact on the academic performance of students with SEN. It was observed that teachers' emotional support and a positive school climate are determining factors for improving academic performance. However, important challenges were identified, such as the lack of specific information and insufficient support from school administrators. In conclusion, the study confirmed that adequate curricular adaptations can significantly improve the academic performance of students with SEN. Recommendations included the need for greater teacher training and more robust support from school administration to ensure the effective implementation of curricular adaptations.